Pengaruh Organisasi Pembelajar terhadap Kompetensi Pegawai Bank - TOBING, SONDANG YOHANNA L.; fitriati, RACHMA (UI Scholars Hub, 2011)
PT Bank Mandiri, Tbk. as the biggest state-owned bank in Indonesia must perform changes and its employees must continuously adapt to its environment in order to exist in its endeavour to be the best in the banking world. This quantitative research uses samples taken randomly from the population of the entire employees of Bank Mandiri central office located in Jakarta. The analysis of the data uses the regression design to perceive the influence of five disciplines of learning organization—i.e. personal mastery, shared vision, mental model, system thinking, and team learning—toward the competence improvement of Mandiri Bank Central Office’s employees in Jakarta, signified by motives, traits, self concept, knowledge, and skill. The result of the research shows that learning organization has a strong relation and a significant influence toward the competence improvement of the employees at Mandiri Bank Central Office in Jakarta.